Myths and facts about the absence of socii in the male genitalia of Larentiinae (Lepidoptera: Geometridae) - Schmidt, Olga (Zootaxa, 2017)
The definition of the term ‘socius’ is evaluated. Considering several recent publications, in which it was assumed that the socii were generally lacking in the male genitalia of the larentiine moths of the family Geometridae, the male genitalic characters of a number of larentiine species representing all the European tribes have been re-examined. The study reveals that the socii are widely present in the European Larentiinae. The presence of the socii in Larentiinae is reviewed. Illustrations of the uncus and socii in the male genitalia of selected species are provided.